Can psychological flexibility discriminate mothers' attachment styles? A study during pregnancy [comunicação oral] - Moreira, Susana (2023)
Psychological flexibility (PF) has been associated with greater well-being, less psychopathology and better parent’s and child’s adjustment (Fonseca et al., 2020; Monteiro et al., 2019). [...]